1975
DOI: 10.1212/wnl.25.2.169
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ketamine in epilepsy

Abstract: Ketamine, a rapid-acting general anesthetic, was administered intravenously to 26 epileptics. The effects of ketamine on the patients' clinical seizures and electroencephalograms were compared with similar periods during alert and sleep states. Epileptic discharges were present in the alert electroencephalogram of 17 (65 percent) of the patients. Epileptic discharges were precipitated or aggravated by sleep in 15 patients (58 percent) and by ketamine in eight patients (31 percent). No siezures were recorded du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

1977
1977
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“… 88 In humans, ketamine has been shown to enhance epileptic discharges, which may explain the rare occurrence of seizures. 89 , 90…”
Section: Discussionmentioning
confidence: 99%
“… 88 In humans, ketamine has been shown to enhance epileptic discharges, which may explain the rare occurrence of seizures. 89 , 90…”
Section: Discussionmentioning
confidence: 99%
“…However, a similar study of human volunteers conducted by Corssen et al [11] rejected this conclusion. These authors found that ketamine did not cause epileptiform discharges in epilepsy patients or in normal subjects and that no evidence was available to support the notion that ketamine could induce or exacerbate convulsions, in contrast with the conclusions of Kayama [12,13].…”
Section: Introductionmentioning
confidence: 93%
“…Some experimental data [122,[229][230][231] and subsequent clinical observations [232] reached similar conclusions. However, the first clinical observations have not always been confirmed [233,234], and a wealth of experimental evidence favors an antiepileptic action ( Table 2). It is still considered to potentially be able to facilitate seizures at low doses, not at doses that will produce sedation or anesthesia [72].…”
Section: Reports On Clinical Usementioning
confidence: 99%